The impact of refugee settlements on land use changes and vegetation degradation in West Nile Sub-region, Uganda - Barasa, Bernard; Mwiru, Aron; Turyabanawe, Loy; Nabalegwa W., Muhamud; Ssentongo, Benard (Geocarto International, 2020)
Uganda continues to experience high-refugee population influx that is beyond the established settlement capacities. Little information is available on the present and future impacts of settling refugees and host-communities on landuse changes and vegetation degradation. This study used Sentinel-2 images (20m) of 2016-2019 and Dinamica Ego-software to determine the current and future spatial areal-extent of changes in 2022. Findings revealed a rarefied increase in areas under subsistence-farming, builtups and refugee-settlements while the losses were seen in savannah-grasslands, wetlands and woodlands. In 2021, the most significant increases in the land will be experienced in builtupareas, settlements and commercial farming. The most degraded vegetation types were savannah-grassland, woodlands and treeplantations. These were primarily attributed to unending activities of deforestation, bush-burning, high-refugee population, land-conflicts with host-communities and wetland reclamation. Thus, unless sustainable farming and energy-saving practices are promoted and adopted, the landscape is likely to remain not even with remnants of green-cover.
Keywords: Refugees; Land use changes; Vegetation degradation; Dinamica Ego; Uganda